Determination of Thermal Comforts Threshold on Students and Domestic Tourists in Lombok Island - Rini Hidayati; Abytia Etika Banja (Agromet, 2018)
The research aims to identify the comfort level on Lombok island, and to determine the comfort threshold values based on various thermal indices for indoor and outdoor. We applied three different indices namely Wet-Bulb Globe Temperature (WBGT), Temperature Humidity Index (THI), and Heat Stress Index (HSI). We observed climate variables including air temperature, relative humidity, wind speed, and black-globe temperature for periode February-March 2018. Then we correlated the indices against comfort and heat perceptions. Our results showed that altitude has influenced on the comfort index. Location on the higher altitude will have low index values, which were consistent for all indices. For the comfort threshold values, adaptation to local climate is the key to determine the values. The adapted people (students) will have a higher threshold value than those whom they were tourists. Our finding revealed that the threshold values for the indices were 28.5, 27.5, 92 for WBGT, THI, HSI, respectively. Based on our statistical analysis, we found that HSI was the best index to determine the comfort level in Lombok for the observed period, as the HSI has strong correlation with comfort and heat perceptions. Further, we recommend the wider used of HSI as the index uses more easily obtained climate variables.